Journey into the net / Malarvili Gopal Krishnan, Meenambigai Bathumalai - Malarvili, Gopal Krishnan; Meenambigai, Bathumalai (2004)
The project entitled "Journey into the Net" (JITN) is an interactive multimedia learning package. A CD-ROM based multimedia learning-teaching application for all level users. The purpose of this package is to introduce Internet to everyone. This project is not involving any hardware or circuit such as home automation controller or hi-tech gadget or even a simple circuit. You can go through them right off your screen. This project involves developing a user interface with a content design and screen design which is link together. At the end of this project, JITN is expected to be such as other interactive multimedia that existence to provide an overview of the Internet especially to users that interested.